Complete Sequences of IncU Plasmids Harboring Quinolone Resistance Genes qnrS2 and aac(6')-Ib-cr in Aeromonas spp. from Ornamental Fish - Dobiasova, Hana; Videnska, Petra; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2016)
The nucleotide sequences of three IncU plasmids from Aeromonas spp. isolated from ornamental fish are described. They had a typical IncU backbone for plasmid replication and maintenance functions, but conjugative transfer modules were disrupted. The gene qnrS2 was inserted into mpR as a mobile insertion cassette. Novel Tn3 family transposons carrying putative toxin-antitoxin and plasmid stability genes were identified. The study demonstrates high plasticity of IncU plasmids from aquatic environments.
Keywords: Animals; Gene Expression Regulation, Bacterial; chinolony; otevřené čtecí rámce; Gram-Negative Bacterial Infections; Quinolones; mikrobiální testy citlivosti; bakteriální proteiny; bakteriální geny; Bacterial Proteins; nemoci ryb; gramnegativní bakteriální infekce; Fish Diseases; Anti-Bacterial Agents; Fishes; transpozibilní elementy DNA; bakteriální léková rezistence; ryby; regulace genové exprese u bakterií; Microbial Sensitivity Tests; DNA Transposable Elements; plazmidy; Sequence Analysis, DNA; Genes, Bacterial; Plasmids; Open Reading Frames; zvířata; sekvenční analýza DNA; antibakteriální látky; Aeromonas; Drug Resistance, Bacterial